Corrosion in Concrete: Inhibitors and Coatings - Coppola, Luigi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Improving the durability of reinforced concrete structures is a mandatory strategy to reduce the environmental impact of construction materials together with aiming to limit carbon dioxide emissions, energy consumption and natural raw materials depletion. Hence, for both new and existing concrete structures, proper protective techniques are required to prevent premature failure induced by environmental aggressive agents. The book presents the most innovative findings both in designing durable new constructions and toward solving durability deficiencies in existing concrete structures, such as innovative special coatings, hydrophobic impregnations and pore blocking treatments that are very efficient in severe aggressive environments (seawater, biocorrosion, etc.). Moreover, migrant corrosion inhibitors applied on concrete surfaces are able to greatly improve resistance against both chloride and CO2. Finally, special reinforcements and fibers, together with a proper designed cathodic protection, can greatly contribute to obtaining long-life reinforced concrete structures, significantly increasing the sustainability of concrete construction.